2012
DOI: 10.1029/2011ja017230
|View full text |Cite
|
Sign up to set email alerts
|

Observations of global ionospheric responses to the 2009 stratospheric sudden warming event by FORMOSAT‐3/COSMIC

Abstract: [1] The global ionospheric response to a stratospheric sudden warming (SSW) is studied using three-dimensional electron density maps derived from radio occultation observations of FORMOSAT-3/COSMIC during the 2009 SSW periods. Results show that the ionospheric electron density at EIA crests exhibit a morning/early afternoon increase followed by an afternoon decrease and an evening increase, indicative of a semidiurnal component during the SSW period, which is consistent with recent studies. The latitude-altitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 44 publications
4
37
0
Order By: Relevance
“…One example of global picture of N m F 2 (a) before, (b) during, and (c) after the SSW2009 at 16 LT. White line in each panel shows geomagnetic equator. Arrows at the top of the figure indicate the longitudes which have been reported by other scientists: 1 Fuller‐Rowell et al [, ]; 2.1 Liu et al []; 2.2 Goncharenko et al [, ]; 3 Liu et al []; 4 Liu et al []; and 5 Xiong et al [] and Lin et al []. The two red squares in Figure b indicate the longitude bands to be studied here (30°E–30°W and 150°E–150°W).…”
Section: Modification Of the Ionosphere Caused By Ssw2009mentioning
confidence: 76%
See 1 more Smart Citation
“…One example of global picture of N m F 2 (a) before, (b) during, and (c) after the SSW2009 at 16 LT. White line in each panel shows geomagnetic equator. Arrows at the top of the figure indicate the longitudes which have been reported by other scientists: 1 Fuller‐Rowell et al [, ]; 2.1 Liu et al []; 2.2 Goncharenko et al [, ]; 3 Liu et al []; 4 Liu et al []; and 5 Xiong et al [] and Lin et al []. The two red squares in Figure b indicate the longitude bands to be studied here (30°E–30°W and 150°E–150°W).…”
Section: Modification Of the Ionosphere Caused By Ssw2009mentioning
confidence: 76%
“…Chau et al [] observed E × B drift velocity of about 30 (m/s) before 8 LT which is higher than that during 09–12 LT for 2008 SSW. Lin et al [] also reported shift of the maximum upward plasma velocity to early morning.…”
Section: Discussionmentioning
confidence: 94%
“…The ionosphere perturbations during SSWs generally exhibit semidiurnal behavior, and variability in the S W 2 has therefore been considered as a potentially important contributor to generating ionospheric variability during SSWs. Observations and model results illustrate that large changes in the S W 2 occur during SSWs [ Fuller‒Rowell et al , ; Jin et al , ; Lin et al , ; Pancheva and Mukhtarov , ; Pedatella et al , ]. These studies have provided substantial evidence that S W 2 perturbations are likely to play a critical role in driving ionosphere variability during SSWs.…”
Section: Introductionmentioning
confidence: 94%
“…It was devoid of any major geomagnetic disturbance which could help interpret the effects due to internal sources. Second, the 2009 SSW event has been studied extensively (Azeem et al, ; Chau et al, ; Conde & Nicolls, ; Fagundes et al, ; Fang et al, ; Forbes & Zhang, ; Fuller‐Rowell, Akmaev, et al, ; Fuller‐Rowell, Wang, et al ; Goncharenko, Coster, et al, ; Goncharenko, Chau, et al, ; He et al, ; Klimenko et al, ; Korenkov et al, ; Lin et al, ; Liu et al, , ; McDonald et al, ; Oyama et al, ; Patra et al, ; Pedatella et al, ), which gives us an advantage to use it as an ideal testbed. However, we must emphasize that none of the studies focused on small‐scale GWs.…”
Section: Introductionmentioning
confidence: 99%